The impact of a humanitarian disaster on the working approach of accountants: a study of contingent effects - Carungu, Jonida; Di Pietra, Roberto; Molinari, Matteo (Emerald, 2021)
Purpose The purpose of this paper is to investigate how a humanitarian disaster as coronavirus disease 2019 (COVID-19) shapes the working approach of accountants. This research is motivated by the call for more in-depth analyses of how COVID-19 affects the work, role and human condition of accountants. The study aims to discover the contingent effects, based on the contingency theory, on accountants' work due to a disaster like COVID-19.